Gestão da inclusão e cultura do acolhimento: desafios para instituições públicas de ensino - Renata de Arruda Câmara Silva; Claudia Thaysa Reis de Moura Santos; Elenilda Rodrigues dos Santos; Lawínya Assíria Amorim Costa; Washington Luiz Alves de Alencar; Maria Célia Soares de Farias; Maria Telma Barbosa Gomes; Jeremias Christian Honorato Costa; Célia Maria Viana Costa; Hildebrando José de Lira; Aureliano Alves da Silva; Alzo Batista de Oliveira; et al. (Revista ft, 2026)
This article analyzes contemporary challenges to inclusion management and the consolidation of a culture of welcoming in public educational institutions from a health and well-being promotion perspective. It is a narrative literature review with a structured search conducted in August 2026, prioritizing Portuguese-language studies published between 2021 and 2026. The analytical corpus comprised 15 articles organized into four axes: management and governance; accessibility and barriers; belonging and school climate; mental health and welcoming practices. Findings show that inclusion goes beyond admission or individual accommodation and requires democratic management, anticipatory accessibility, confrontation of attitudinal barriers, multiprofessional support, and monitoring. Recent studies associate belonging and participation with more welcoming environments and lower emotional distress, while higher education research links academic integration and psychosocial support to mental health. The study concludes that a culture of welcoming should be institutionalized as a management policy, with defined responsibilities, resources, workflows, and indicators, integrating education, student assistance, and health to strengthen retention, participation, learning, and equity.